Evaluating LSTM Networks, HMM and WFST in Malay Part-of-Speech Tagging - Tan, Tien-Ping; Bali, Ranaivo-Malancon; Besacier, Laurent; Yeong, Yin-Lai; Keng, Hoon Gan; Enya, Kong Tang (Universiti Teknikal Malaysia (UTEM), 2017)
Tien-Ping Tan1, Bali Ranaivo-Malançon2, Laurent Besacier3, Yin-Lai Yeong1, Keng Hoon Gan1, and Enya Kong Tang1